2023
DOI: 10.3390/s23031299
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pitch Dimensions during Small-Sided Games to Reach Match Physical and Physiological Demands on the Youth Soccer Players

Abstract: The aims of this study were to (i) analyze the physical and physiological responses of four matches competition and (ii) to investigate the relationships among three different pitch dimensions of small-sided game (SSG) on the youth soccer players. Fifteen male U19 soccer players (age 17.3 ± 0.5 years, height 175.7 ± 5.6 cm, weight 68.5 ± 8.6 kg, playing experience 7.8 ± 1.4 years) were randomly assigned to three play areas: small (50 m2), medium (SSG-m, 150 m2) and large (SSG-l, 250 m2) area per player includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The study also found no significant correlation between pitch ratio per player and TGs intensity, with an average intensity of 1.20 ± 0.29 AU observed in TGs and no significant differences in intensity between TGs and official matches. These findings are consistent with previous literature on the physiological demands of TGs and official matches in soccer ( Casamichana et al, 2012 ; Beato et al, 2023a ; Castillo-Rodríguez et al, 2023 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study also found no significant correlation between pitch ratio per player and TGs intensity, with an average intensity of 1.20 ± 0.29 AU observed in TGs and no significant differences in intensity between TGs and official matches. These findings are consistent with previous literature on the physiological demands of TGs and official matches in soccer ( Casamichana et al, 2012 ; Beato et al, 2023a ; Castillo-Rodríguez et al, 2023 ).…”
Section: Discussionsupporting
confidence: 93%
“…Against this backdrop, the results of this study provide valuable insights into the potential use of MP and ED as reliable indicators of the differences between TGs and official matches. The ApP and intensity are two factors to consider when designing the TGs, as they can affect the players’ physiological and performance demands, technical and tactical abilities, and overall experience during the training process ( Kelly and Drust, 2009 ; Casamichana et al, 2018 ; Riboli et al, 2020 ; Castillo-Rodríguez et al, 2023 ; Clemente et al, 2023 ). Interestingly, no significant correlation was observed between pitch ratio per player and TGs intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Existe un incremento de estudios sobre los SSG, que consideran el estudio de diferentes tamaños, relaciones de jugadores y tiempos para conocer los efectos sobre la demanda física, las respuestas fisiológicas (Castillo-Rodríguez et al, 2023), así como acciones técnicas y comportamientos tácticos Clemente et al, 2023). Así mismo, el estudio de los SSG ha considerado el estudio del nivel deportivo de los jugadores, con propuestas que van desde la evaluación de comportamiento exploratorio para evaluar la creatividad en niños (Canton et al, 2021), comportamientos tácticos en jugadores jóvenes y juveniles , jugadores semiprofesionales (Casamichana et al, 2012), variabilidad y creatividad en jugadores élite (Caso & Van der Kamp, 2020), propuestas para mejorar el rendimiento físico y la composición corporal a partir de entrenamientos de alta intensidad basado en la carrera (Nayıroğlu et al, 2022;Papancrová et al, 2024).…”
Section: Conclusionesunclassified